(3ofhQ GdWQa hnfhoQ GdWQas - (3EHQGgje Hf Ydj Hf Jeje GdCfUGQj, CHh ESMGb GdMUQj,J (B453 (3g` s
(3ChdgG (B:s
(3CeG HYO hUd Gddg dSjOj GdLdjd, LfGM GdUfY GdLejd CeQJ ajg CYdi Gddg CeQc, hCSfi bOQc s
(3BNQgG (B:s
(3hdh cfJ djdkG cfJ beQGA oLfHJ fMhS djGdj GdTgQ, Ch djdI GdbOQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3JYGhQ YdjgG fGSNGf hHgG WjGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B50 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B8s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B178 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1983s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(39(1)) s
Keywords: (3GdCOHs